2017
DOI: 10.1016/j.jad.2016.09.036
|View full text |Cite|
|
Sign up to set email alerts
|

Analysing UK clinicians’ understanding of cognitive symptoms in major depression: A survey of primary care physicians and psychiatrists

Abstract: Background: Cognitive dysfunction occurs in depression and can persist into remission. It impacts on patient functioning but remains largely unrecognised, unmonitored and untreated. We explored understanding of cognitive dysfunction in depression among UK clinicians.Methods: A multi-step consultation process.Step 1: a multi-stakeholder steering committee identified key themes of burden, detection and management of cognitive dysfunction in depression, and developed statements on each to explore understanding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This finding is consistent with the results of several studies reporting persistence of cognitive symptoms in the remission phase (12, 25). The lower reporting of cognitive symptoms by HCPs in the remission phase could indicate less awareness and/or attention to these symptoms, as previously suggested by a survey of PCPs and psychiatrists in the United Kingdom (26). As cognitive symptoms of MDD are associated with psychosocial and functional impairment, low quality of life (4), and a higher risk of relapse (16), it is important that such symptoms are identified and managed.…”
Section: Discussionmentioning
confidence: 60%
“…This finding is consistent with the results of several studies reporting persistence of cognitive symptoms in the remission phase (12, 25). The lower reporting of cognitive symptoms by HCPs in the remission phase could indicate less awareness and/or attention to these symptoms, as previously suggested by a survey of PCPs and psychiatrists in the United Kingdom (26). As cognitive symptoms of MDD are associated with psychosocial and functional impairment, low quality of life (4), and a higher risk of relapse (16), it is important that such symptoms are identified and managed.…”
Section: Discussionmentioning
confidence: 60%
“…Patient-centered consulting approaches allow treatment to be based on individual patient symptoms and preferences, which may result in improved outcomes (36,37). Other studies have also reported low recognition by HCPs of cognitive symptoms in patients with MDD (38)(39)(40). A survey of Italian psychiatrists showed that, although psychiatrists considered cognitive symptoms among the most relevant residual symptoms in MDD, these symptoms were not always taken into consideration when selecting antidepressant therapy (38).…”
Section: Discussionmentioning
confidence: 99%
“…22 Currently, there is no consensus about the best tools or test battery to accurately and efficiently assess cognitive impairment associated with depression in clinical practice. Nor are there data to refute or confirm that the same tools can be used in younger and older adults, male and female.…”
Section: The Needsmentioning
confidence: 99%